1994
DOI: 10.3758/bf03209250
|View full text |Cite
|
Sign up to set email alerts
|

Substituting new details for old? Effects of delaying postevent information on infant memory

Abstract: How that which we remember is selectively distorted by new information was studied in 3-month-old infants who learned to move a particular crib mobile by operant foot kicking. Infants who were passively exposed to a novel mobile 1, 2, or 3 days later subsequently treated the novel mobile as if they had actually been trained with it. Also, after the longest exposure delay, they no longer recognized the original mobile. Likewise, when the novel mobile was exposed after the longest delay, it could prime the forgo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
41
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 58 publications
4
41
0
Order By: Relevance
“…Research with both infants and adults has found that the original memory is modified more easily when it is older (Belli, Windschitl, McCarthy, & Winfrey, 1992;Boller et al, 1996;Loftus, Miller, & Burns, 1978;Muzzio & RoveeCollier, 1996;Rovee-Collier et al, 1994). In Experiment 2, therefore, we examined the possibility that the age of a reactivated memory might influence its malleability.…”
Section: Experiments 2: Age Of the Reactivated Memorymentioning
confidence: 99%
See 2 more Smart Citations
“…Research with both infants and adults has found that the original memory is modified more easily when it is older (Belli, Windschitl, McCarthy, & Winfrey, 1992;Boller et al, 1996;Loftus, Miller, & Burns, 1978;Muzzio & RoveeCollier, 1996;Rovee-Collier et al, 1994). In Experiment 2, therefore, we examined the possibility that the age of a reactivated memory might influence its malleability.…”
Section: Experiments 2: Age Of the Reactivated Memorymentioning
confidence: 99%
“…During this time, their memory of the training mobile is highly specific and cannot be retrieved by a generalized cue. Once infants have forgotten the details of the original mobile, however, the details of a novel mobile can be substituted for the details of the original mobile in the training memory, producing a permanent memory modification (Boller et al, 1996;Muzzio & Rovee-Collier, 1996;Rovee-Collier et al, 1994). Likewise, 6-month-olds who learn to move the mobile in a distinctive context remember the details of that particular context and discriminate it from a novel context for 3 to 5 days after training.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Second, experiments were conducted at each infant's home. Some studies 56,57 have shown the importance of context for learning and memory in this paradigm. Additional research is needed to determine whether these results generalize to a clinical setting.…”
Section: Limitationsmentioning
confidence: 99%
“…Because their memory of the familiar training stimulus was presumably strongest at this time, we predicted that infants of both ages would look longer at the novel mobile and also would kick signi®cantly above baseline. In addition, when we had previously tested 3-month-olds with either a novel mobile or the training (familiar) mobile 3 to 4 days after training, they had treated them equivalently, responding as robustly to the novel mobile as to the familiar training one (Rovee-Collier, Adler, & Borza, 1994;Rovee-Collier & Sullivan, 1980). In Experiment 3, therefore, we also gave a group of 3-montholds a paired-comparison test 4 days after the end of training and predicted that they also would kick robustly, evidencing operant retention, but would treat the novel and familiar mobiles equivalently and look at them nondifferentially (A corresponding group of 6-month-olds was not tested because infants of this age operantly discriminate a novel mobile from the training one for 2 weeks, which is the longest delay that they also exhibit operant retention; Borovsky & Rovee-Collier, 1990;Hill et al, 1988).…”
Section: Experiments 3: Testing Immediately (3 and 6 Months) And Aftermentioning
confidence: 99%